Identity-based identification without random oracles - Kurosawa, Kaoru; Heng, Swee Huay (Springer, 2005)
This paper shows identity-based (ID-based) identification schemes which are provably secure in the standard model. The schemes are derived from Boneh-Boyen signature scheme, a signature scheme which is provably secure in the standard model based on the strong Diffie-Hellman assumption. More precisely, we present two canonical schemes, namely, a scheme which is secure against impersonation under passive attack, and a scheme which is secure against impersonation under active and concurrent attacks.